Penyuluhan Pentingnya Laporan Keberlanjutan Bagi Usaha Mikro Kecil Menengah Dalam Rangka Mempertahankan Keberlanjutan Usaha - Nelli Novyarni; Kustri Andyarini; Rini Ratnaningsih; Reni Harni (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
The problem for MSMEs is how to understand and implement Sustainability Reporting properly. The goal of this community service is to be able to meet MSME needs for availability of sustainability reports and exchange of business information with parties inside and outside the MSME. The method used is interactive, and the result of this crowdsourcing works well. where MSMEs can prepare simple sustainability reports well and need ongoing guidance. The conclusion of this crowdsourcing is that MSMEs understand and can perform simple Sustainability Reporting using the Sustainability Reporting app.